The effect of thyroidectomy on conception rates, offspring numbers, and histopathology of ovarium and uterus in rats - Timurkaan, N; Risvanli, LA (Indian Veterinary Journal, 2004)
Thyroid glands lie on the first and second circles on larynx and release totally four hormones, that are viz: (T-3), thyroxine (T-4), reverse triiodothyronine (rT(3)) and calcitonin. The most important function of thyroid hormones is to increase metabolism rate of the tissues. Besides this, thyroid hormones have important effects on breast development, milk production and release, as well as reproductive activities. But the effect of these hormones on gonads has not completely elucidated. However, these hormones have been reported to function by directly influencing on meta-bolism of gonads or by influencing on release of adenohypophyseal hormones which control functions of these tissues. (Chester, 1987; Forrester and Monroe, 1997; Yilmaz, 1999). In this study, it was aimed to investigate the effect of hypothyroidism induced with thyroidectomy in rats on conception rates, offspring numbers, and histopatnology of ovarium and uterus.
Keywords: Hypothyroid Rats